2013
DOI: 10.1371/journal.pone.0062552
|View full text |Cite
|
Sign up to set email alerts
|

Variability of HIV-1 Genomes among Children and Adolescents from São Paulo, Brazil

Abstract: BackgroundGenetic variability is a major feature of the human immunodeficiency virus type 1 (HIV-1) and considered the key factor to frustrating efforts to halt the virus epidemic. In this study, we aimed to investigate the genetic variability of HIV-1 strains among children and adolescents born from 1992 to 2009 in the state of Sao Paulo, Brazil.MethodologyPlasma and peripheral blood mononuclear cells (PBMC) were collected from 51 HIV-1-positive children and adolescents on ART followed between September 1992 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
18
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 53 publications
5
18
1
Order By: Relevance
“…There is no vaccine against HIV, and AIDS is still a major public health challenge, aggravated by the possibility of co-infection of HIV and Hepatitis B and C viruses. Such diseases share the same forms of transmission, and clinical studies conducted in Brazil show that, among HIV/AIDS-infected individuals, almost 6% are positive for HBV and from 5 to 18% are positive for HCV (10).…”
Section: ▄ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no vaccine against HIV, and AIDS is still a major public health challenge, aggravated by the possibility of co-infection of HIV and Hepatitis B and C viruses. Such diseases share the same forms of transmission, and clinical studies conducted in Brazil show that, among HIV/AIDS-infected individuals, almost 6% are positive for HBV and from 5 to 18% are positive for HCV (10).…”
Section: ▄ Introductionmentioning
confidence: 99%
“…Another important issue is related to the fact that HIV has mutated, and diagnostic tests -especially rapid tests used in the first hours after the accident -need to be more sensitive and specific in order to track the current genetic diversity 10 . Dental schools are faced with a big challenge in seeking better strategies to raise awareness and self-efficacy, among dental students and the entire community of teachers and counselors, to avoid the threats occupational exposures to biological material may pose.…”
Section: ▄ Introductionmentioning
confidence: 99%
“…Similar findings were found when more than one genomic region was evaluated. [10][11][12] The sequences of all mother-child pairs were in subtype accordance, including those harboring BF recombinant strains. It is likely that the recombinants exhibit some advantages over parental strains with regard to any changes in tropism and viral fitness, making them potentially more virulent and more efficiently transmitted.…”
mentioning
confidence: 97%
“…There is no vaccine against HIV, and AIDS is a disease that continues to be a challenge to public health, with 37 thousand new cases per annum in Brazil, of which 7 thousand occur in the State of São Paulo 20 . Recent studies have shown that the AIDS virus has undergone mutations 21 . The diagnostic tests -especially the fast tests used in the first hours after the accident -would need to be more sensitive and specific to trace the contemporary genetic diversity.…”
Section: Resultsmentioning
confidence: 99%